RISIKO IBU HAMIL KURANG ENERGI KRONIS (KEK) DAN ANEMIA UNTUK MELAHIRKAN BAYI DENGAN BERAT BADAN LAHIR RENDAH (BBLR) - Edwi Saraswati; Iman Sumarno (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1998)
An observation was done to study the relationship between Chronic Energy Malnutrition (CEM) and Anemic pregnant women with the risk of delivering Low Birth Weight babies (LBW). The observation was carried out in four District in West Java among women suffered from CEM or and Anemic in fourth to ninth months of pregnancy. The result showed that anemic women having HB content of 11.0 g/dl did not have any risk of delivering UWB because since HB content at such a degree did not yet affect the hormonal and physiological functions of pregnant women. Neither did the Chronic Energy Malnutrition at degree of mid-upper-arm circumference 23.5 cm. Several lower degrees of CEM and anemia, lower than those mentioned above were statistically examined to study the risk of delivering LBW. The results showed that pregnant women having Mid-upper-arm circumference (MUAC) of less than 23.0 cm had high risk to deliver as high as LBW 232 percent higher than those with MUAC more than 23.0 cm. Pregnant women having HB less than 10.0 g/dl had the risk of delivering LBW 255 percent higher than those having HB more than 10.0 g/dl. Women who had experienced miscarriages were at the risk of delivering LBW 2.81 times higher than those who had not. Those who had been delivering still-born babies were at the risk of delivering LBW 4.35 times higher than those who had never been delivery. To minimize the risk of LBW effort should be made to improve the nutritional status of women and to cure malnutrition and anemia prior to pregnancy. Women who had experienced miscarriages or had still-born babies should be in good condition and have good nourishment before the subsequent pregnancy.Keywords: chronic energy malnutrition (CEM), anemic pregnant women, low birth weight